Bermain dengan Batik sebagai Media Pembelajaran Mulok pada Siswa Sekolah Dasar - Aan Sudarwanto; Bagus Indrayana; Kuntadi Wasi Darmojo (Abdi Seni, 2022)
This article summarizes the community service (PKM) thematic activities by a group from ISI Surakarta. The activities aim to increase children’s knowledge about batik which is then used as a medium for Mulok (local content curriculum) learning. The rationale for this activity is the importance of providing local content material rooted in cultures and traditions in the students’ area, to defend their national identity from the huge influence of foreign cultural developments or new cultures existing in their environment. Providing local content material as part of character education, the activities helps students to understand batik as a product of Indonesian culture. Batik learning needs to be introduced to elementary school children, especially in batik center areas such as in Surakarta city, which has to do with continuity and preservation. The focus of this PkM activity is more directed to aspects of improving the quality of learning with a character education model. The results of this thematic community service or PkM show that after training and assistance, the students are more knowledgeable about batik. In addition, there created teaching media for batik knowledge based on works of art. Furthermore, a local content learning strategy emerged as a knowledge base developed by SBK (Culture and Art) subject teachers at Tugu Jebres Elementary Public School, Surakarta.